China's Digital Silk Road: The Loss for Indonesia - Blestri Jasuma, Nanda; Kusuma Paksi, Arie (Nation State: Journal of International Studies, 2021)
One of China’s great projects in the current digital era, namely the Digital Silk Road (DSR) project, merits an examination from a Gramscian lens. While liberals are talking about how this project can beneficially the partner’s country, Gramsci’s thought can provide the other perspective in understanding how this project can give unexpected costs for the partner country. As the biggest market in Southeast Asia’s country, Indonesia is worth the attention related to this issue as this country has become one of the strategic partners of China’s DSR. However, DSR is offering both economic benefits and multi-faceted costs simultaneously for Indonesia. Hence, this study argues that the DSR project, in Gramsci lens, is giving a push for China to spread its hegemony and take over the domination in the Indonesian economy. This study is supported by the qualitative research method with the data is collected through secondary data and literature review.